Virucidal and Synergistic Activity of Polyphenol-Rich Extracts of Seaweeds against Measles Virus - Morán Santibáñez, Karla Selene; Peña Hernández, Mario A.; Cruz Suárez, Lucía Elizabeth; Ricque Marie, Denis; Skouta, Rachid; Vasquez, Abimael H.; Rodríguez Padilla, María Cristina; Trejo Ávila, Laura M. (2018)
Abstract: Although preventable by vaccination, Measles still causes thousands of deaths among young children worldwide. The discovery of new antivirals is a good approach to control new outbreaks that cause such death. In this study, we tested the antiviral activity against Measles virus (MeV)ofPolyphenol-richextracts(PPs)comingfromﬁveseaweedscollectedandcultivatedinMexico. AnMTTassaywasperformedtodeterminecytotoxicityeffect,andantiviralactivitywasmeasuredby syncytia reduction assay and conﬁrmed by qPCR. PPs from Ecklonia arborea (formerly Eisenia arborea, Phaeophyceae) and Solieriaﬁliformis (Rhodophyta) showed the highest Selectivity Index (SI), >3750 and >576.9 respectively. Both PPs extracts were selected to the subsequent experiments owing to their high efﬁcacy and low cytotoxicity compared with ribavirin (SI of 11.57). The combinational effect of PPs with sulphated polysaccharides (SPs) and ribavirin were calculated by using Compusyn software. SynergisticactivitywasobservedbycombiningbothPPswithlowconcentrationsofSolieria ﬁliformis SPs (0.01 µg/mL). The antiviral activity of the best combinations was conﬁrmed by qPCR. Virucidal assay, time of addition, and viral penetration evaluations suggested that PPs act mainly by inactivating the viral particle. To our knowledge, this is the ﬁrst report of the virucidal effect of Polyphenol-rich extracts of seaweeds.